Castle Adventure Supplementary Reading Material - Hunt, Roderick (China Oxford University Press, 2012)
Biff, Chip, Kipper, and Nadim are taken on a magical adventure to a medieval castle. Inside, they help a prisoner escape from the guards by outsmarting them. With teamwork and courage, they complete the rescue just before the magic key takes them back home.